Como cuido do meu filho desnutrido: abordagem cultural - Frota, Mirna Albuquerque (1998)
The malnutrition is considered the largest cause of the infantile mortality. In the great majority of the cases, it is tied up to the difficult condition socioeconomic living in the daily, to the life way, faiths and the mothers' values and to the way of taking care of the undernourished child. This study had for objectives: to describe the adolescent mother's cultural context and the undernourished child's care; to contribute for the qualification of the health professionals’ exercise in a cultural approach. The informers were the adolescent mothers that accompanied its children intemed at the Institute of Prevention to the Malnutrition and Excepcionality (IPREDE), in the period from july/97 to august/98. Bases on the presuppositions of the etnonursing according to the Theory of Universality and Cultural Diversity of the Care (LEININGER,1991). The collection of data was based in the observation - participation - reflection model. The data were classified and analyzed, having emerged the cultural theme: How I take care of my undernourished child. The results reveal that, in its majority, the adolescent mothers are shown confused and anxious in the care with the undernourished child, demonstrating attempts and forms of taking care, that empty space from the empiric knowledge, in search of the Services of health. This way, it is important the cultural focus of the care, objectifying a complete attendance and, consequently, larger satisfaction of specific segments of the population so marked by sociocultural problems.